Seasonal and Growth‐Dependent Dynamics of Bacterial Community in Radish Sprouts. Issue 3 (12th January 2016) - Asakura, Hiroshi; Tachibana, Masato; Taguchi, Masumi; Hiroi, Toyoko; Kurazono, Hisao; Makino, Sou‐Ichi; Kasuga, Fumiko; Igimi, Shizunobu
Abstract: Bacterial counts of 170 radish sprout ( Raphanus sativus ) retailed in Japan between June 2012 and February 2013 was examined. Aerobic plate counts and coliform counts exhibited seasonal variations. No Shiga toxin‐producing Escherichia coli or Salmonella spp. were detected from them. 16S rRNA pyrosequencing analysis of 16 representative samples from one farm (farm D) revealed a predominance of Pseudomonas spp. throughout seasons, and summer samples exhibited an increase in Enterobacteriaceae including Escherichia spp. and decreases in Oxalobacteraceae (primarily Duganella and Janthinobacterium spp.) and Flavobacteriaceae ( Flavobacterium spp.) compared with winter samples. Quantitative‐PCR analysis of 40 samples from the farm D confirmed the seasonal dynamics of E. coli and Flavobacterium spp. Radish seeds increased proportion of Pseudomonas spp. after sprouting, compared with pre‐sprouted seeds, suggesting that increased proportion of Pseudomonas spp. in retailed samples might be sourced from their seeds. Our data thus provides that atmospheric control at postsprouting stage might be hygienic practical point to secure microbial safety. Practical Applications: Fresh sprouts are common vehicles of foodborne pathogens that have been responsible for much numbers of outbreaks worldwide. Through the use of indicator bacterial counts in combination with metagenomic approaches, we confirmed the seasonal and growth‐dependent variation of bacterial community structure in retailed radish sprouts. Information and relief provided to manufacturers/consumers could help to secure microbial safety associated with fresh sprouts.